Insights into Low-risk Gestational Trophoblastic Neoplasia from a Tertiary Care Institute in India: A Short Communication - Gupta, Sumedha; Kalra, Kaushal; Kalwaniya, Dheer Singh (Asian Pacific Journal of Cancer Care, 2025)
Objective: To report clinical characteristics, treatment outcomes and chemotherapy-related toxicities in patients with low-risk GTN at tertiary care centre in India. Material and methods: This retrospective observational study was conducted at the Department of Medical Oncology of Vardhman Mahavir Medical College and Safdarjung Hospital, New Delhi over 2 years. From December 2021 to December 2023, the medical records of all the patients diagnosed with GTN were retrospectively analyzed for clinical and treatment details. Low-risk GTN patients received methotrexate (MTX) with folinic acid (FA) rescue. The Chemotherapy regimen for Low-risk GTN resistant to first-line chemotherapy had received multiagent chemotherapy EMA-CO every 2 weeks. Results: Of the 40 patients with low-risk GTN, only 35 women were available for evaluation as 5 were lost to follow-up during the treatment period. The study found that the majority of patients (71.4%) experienced a molar pregnancy before developing gestational trophoblastic neoplasia (GTN), with 91.4% developing GTN within the first 4 months. Of these, 32 patients achieved complete responses (91.4%), while 3 experienced treatment failure (8.5%). All three patients who failed primary MTX therapy were subsequently treated with multiagent chemotherapy and achieved complete remission (CR). Overall survival (OS) and cure rates for all patients with low-risk GTN were 100%. Conclusion: The MTX regimen was remarkably effective in treating women with low-risk GTN, achieving a complete response (CR) rate of 91.4% without encountering severe adverse effects.